The relationship of knowledge level of class xii students with attitude to hiv/aids prevention in the same state 9 regency of tangerang 2022 - Sabda Azis, Rohmi; Taufiq, Mizwar; Karim, Abdul (Yayasan Pusat Pendidikan Vanchapo, 2023)
The existence of different levels of knowledge about sex will cause different attitudes towards sex itself, which in turn affects sexual behavior. The negative impact of free sex cannot be separated from the individual's attitude towards free sex. A high level of knowledge about HIV/AIDS can make adolescents have a positive attitude to prevent HIV/AIDS. The author is interested in conducting research on